2020
DOI: 10.2139/ssrn.3685933
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Families to Protect Child Health: Parenting Quality and Household Needs During the COVID-19 Pandemic

Abstract: Background: Supportive parenting is critical for promoting healthy child development in the face of stressors, such as those occurring during COVID-19. Here, we address a knowledge gap regarding specific household risk factors associated with parenting quality during the pandemic and incorporate first-person accounts of family challenges and needs. Methods: Mixed methods were applied to data collected between April 14th-28th, 2020 from the "Parenting During the Pandemic" survey. Participants included 656 prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The participants in the current study are Latina mothers, and the economic and psychological toll may not be limited to their own well-being. Increasing caregiving responsibilities and decreasing psychological and economic resources may have repercussions on caregiving quality and children’s health (Roos et al, 2020). Specifically, theoretical and empirical research show that parents’ psychological distress often spills over to impact their ability to provide sensitive and responsive care to their children, potentially jeopardizing child well-being (Conger et al, 2012; McLoyd, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the current study are Latina mothers, and the economic and psychological toll may not be limited to their own well-being. Increasing caregiving responsibilities and decreasing psychological and economic resources may have repercussions on caregiving quality and children’s health (Roos et al, 2020). Specifically, theoretical and empirical research show that parents’ psychological distress often spills over to impact their ability to provide sensitive and responsive care to their children, potentially jeopardizing child well-being (Conger et al, 2012; McLoyd, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The confluence of these factors heightens parenting stress and increase the risk for parental burnout (Davidson et al., 2020 ). Parental stress/burnout and other mental health concerns, such as depression and anxiety, are detrimental to children's well‐being because they contribute to low‐quality parenting during the pandemic (Roos et al., 2020 ). This is problematic because high‐quality parenting, marked by parental awareness of children's needs and the use of sensitive and responsive caregiving strategies, underlies optimal child development (Griffith, 2020 ; Maggi et al., 2010 ; World Health Organization and Department of Child and Adolescent Health and Development, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found more "low-quality" parenting as evidenced by more stress, more negative parenting behaviors, and less positive parenting behaviors. Parents also reported feeling doubt about their parenting and teaching abilities during the pandemic (Roos et al, 2021). Van Tilburg et al (2020) also surveyed parents and found, not surprisingly, high rates of stress, clinical anxiety, and depression among parents.…”
Section: Parenting During a Pandemicmentioning
confidence: 99%
“…Even parents with educational training have found schooling during the pandemic difficult (Harris, 2020). Roos et al (2021) surveyed parents regarding the quality of their parenting during the pandemic. They found more "low-quality" parenting as evidenced by more stress, more negative parenting behaviors, and less positive parenting behaviors.…”
Section: Parenting During a Pandemicmentioning
confidence: 99%